Relações familiares, processos de identificação e bem-estar em adolescentes cumprindo medida socioeducativa com restrição de liberdade - Angélica Maria Fereira de Melo Silva (2012)
Among the risk factors that cause criminal behavior, it is known that the family has great importance for being the primary socialization environment of man. In this sense, the objective of this thesis was to conduct two studies about the relationship between the family system and the transgression behavior of adolescents. The first of these studies is a systematic review in which it was used seven databases: SciELO, LILACS; BVS; PePSIC; PsycNET; APA PsycNET; Science Direct and Web of Knowledge. The results showed that family factors have been considered by the scientific literature as an important factor in understanding the encouragement of criminal tendencies; however it is not the existence of a risk factor that will determine the action for violations of the law. The second, aimed to analyze family relationships, the processes of identification and subjective well-being in adolescents in conflict with the law. For this purpose, the sample was composed from two groups: 30 adolescents in conflict with the law in self-restrain measures and 30 adolescents without conflict with the law, with ages ranging from 12 to 17 years from both sexes. There were used as instruments: the sociodemographic questionnaire, Familiogram, identification family test, positive and negative scale of affection and life satisfaction scale. As a result, it was found that institutionalized adolescents had lower levels of subjective well-being and an idealization of their family system, in addition to obtaining a regression model that explained 44% of the variance of subjective well-being. Therefore, this study advances by allow clarifications of these factors, and add that the effectiveness of programs to reduce violence must start and continue during the childhood and adolescence.